Numerical and experimental methods used to evaluate active drag in swimming: A systematic narrative review - Lopes, T. J.; Morais, J. E.; Pinto, M. P.; Marinho, D. A. (Frontiers in Physiology, 2022)
Introduction: In swimming, it is necessary to understand and identify the main factors that are important to reduce active drag and, consequently, improve the performance of swimmers. However, there is no up-to-date review in the literature clarifying this topic. Thus, a systematic narrative review was performed to update the body of knowledge on active drag in swimming through numerical and experimental methods.